2010
DOI: 10.1111/j.1365-2435.2009.01672.x
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐trait test of the leaf‐height‐seed plant strategy scheme with 133 species from a pine forest flora

Abstract: Summary1. Westoby's [Plant and Soil (1998), 199, 213] Leaf-Height-Seed (LHS) plant strategy scheme quantifies the strategy of a plant based on its location in a three-dimensional space defined by three functional traits: specific leaf area (SLA), height, and seed mass. This scheme is based on aboveground traits and may neglect strategies of belowground resource capture if root functioning is not mirrored in any of the axes. How then do fine roots fit into the LHS scheme? 2. We measured 10 functional traits on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
182
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(204 citation statements)
references
References 58 publications
15
182
1
6
Order By: Relevance
“…Studies have made some headway in examining whether parallel trade-offs occur belowground, but general trends are elusive. For example, higher specific root length (SRL) indicates greater absorptive root length per unit biomass and, like SLA, has been linked to other attributes associated with rapid resource acquisition, such as high root respiration rate (Tjoelker et al, 2005) and low root lifespan (Eissenstat et al, 2000;McCormack et al, 2012) as well as rapid aboveground growth rates and associated leaf traits (Reich et al, 1998a;Wright & Westoby, 1999;Laughlin et al, 2010;Liu et al, 2010). However, other studies have not found correlations between SRL and growth rate metrics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have made some headway in examining whether parallel trade-offs occur belowground, but general trends are elusive. For example, higher specific root length (SRL) indicates greater absorptive root length per unit biomass and, like SLA, has been linked to other attributes associated with rapid resource acquisition, such as high root respiration rate (Tjoelker et al, 2005) and low root lifespan (Eissenstat et al, 2000;McCormack et al, 2012) as well as rapid aboveground growth rates and associated leaf traits (Reich et al, 1998a;Wright & Westoby, 1999;Laughlin et al, 2010;Liu et al, 2010). However, other studies have not found correlations between SRL and growth rate metrics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that there are considerable overlaps for the plant trait ranges among different plant functional types, while variations in plant traits within a PFT can be larger than the differences in means of different PFTs (Verheijen et al, 2013;Wright et al, 2005;Laughlin et al, 2010). Therefore, for simplicity, we applied only the PFT of C 3 grass with a shallower rooting depth to represent the average of vegetation growing in northern peatlands.…”
Section: Modified Peat Plant Parametersmentioning
confidence: 99%
“…We measured specific leaf area (SLA), leaf dry matter content (LDMC), leaf nitrogen concentration ([N]), fine root [N], seed mass, specific root length (SRL), canopy height, and mean Julian flowering date. Trait measurement methodology is described in Laughlin et al (2010).…”
Section: Functional Traitsmentioning
confidence: 99%
“…In prior work, we found that three orthogonal strategy axes, representing Westoby's (1998) ''leaf-height-seed'' model of plant strategies, captures the majority of functional variation in a ponderosa pine forest understory flora (Laughlin et al 2010). The first strategy axis represents variation along the ''leaf economics spectrum'' (Wright et al 2004) and is indicative of a species' ability to rapidly photosynthesize and respond to opportunities for rapid growth (Reich et al 1997).…”
Section: Introductionmentioning
confidence: 99%